2017
DOI: 10.1161/circresaha.117.311603
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and the Risk of Atherosclerotic Cardiovascular Morbidity and Mortality

Abstract: Rationale: Thyroid hormones have been linked with various proatherogenic and antiatherogenic processes. However, the relationship of thyroid function with manifestations of atherosclerosis remains unclear. Objective: To investigate the association of thyroid function with atherosclerosis throughout its spectrum; that is, subclinical atherosclerosis, incident atherosclerotic cardiovascular (ASCV) events, and ASCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 38 publications
3
66
1
3
Order By: Relevance
“…Cardiovascular mortality was defined as death due to CHD, cerebrovascular disease or other cardiovascular diseases, as previously described. (2,23) The ascertainment of cardiovascular mortality in the Rotterdam Study has been extensively described in a previous study. (23) In short, information on cardiovascular mortality is obtained from municipality records, general practitioners and reports of medical specialists.…”
Section: Assessment Of Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular mortality was defined as death due to CHD, cerebrovascular disease or other cardiovascular diseases, as previously described. (2,23) The ascertainment of cardiovascular mortality in the Rotterdam Study has been extensively described in a previous study. (23) In short, information on cardiovascular mortality is obtained from municipality records, general practitioners and reports of medical specialists.…”
Section: Assessment Of Cardiovascular Diseasementioning
confidence: 99%
“…(1) To date, population-based studies among middle-aged and older adults have shown that high and high-normal thyroid hormone levels are associated with an increased risk of cardiovascular disease and mortality, independent of traditional cardiovascular risk factors as hyperlipidemia, hypertension, diabetes, and obesity. (2)(3)(4) This points towards other factors that can mediate the increased cardiovascular risk in case of excess thyroid hormones. The identification of these mediating factors is essential to better understand the role of thyroid hormones in cardiovascular disease, as well as to identify potential targets for future preventive strategies.…”
mentioning
confidence: 96%
“…Observational studies have shown that even thyroid hormone levels within the normal range are associated with subclinical atherosclerosis, as assessed by coronary artery calcification score and the overall risk of adverse atherosclerotic cardiovascular events, including fatal and nonfatal myocardial infarction, other CAD mortality and stroke (10). However, several large population-based studies investigated the association between variation in normal range thyroid function and the CAD risk only, and did not find an association (8, 4547).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas smoking, hypertension, diabetes, obesity and dyslipidaemia are the major modifiable cardiovascular risk factors(2), observational studies have demonstrated that also overt and subclinical thyroid dysfunction are associated with a higher risk of CVD(36). Moreover, even variation in thyroid function within the normal range has been associated with an increased risk of CVD, including atherosclerotic disease and stroke (710). This poses the question as to whether common forms of mild thyroid dysfunction (with a prevalence of 5-10 % in the general population) should be treated to prevent these complications.…”
Section: Introductionmentioning
confidence: 99%
“…Як відомо, ССЗ і хвороби периферійних судин є причиною значно більш високої захворюваності і смертності в пацієнтів із гіпотиреозом, ніж класична тріада: нефропатія, нейропатія, ретинопатія, хоча небезпека цих захворювань також дуже висока. Тобто, наявність гіпотиреозу і асоційованих із ним клініко-метаболічних порушень істотно підвищує ризик серцево-судинних захворювань (ССЗ) [20]. Аналіз чинників ризику розвитку ССЗ у жінок із клімактеричним синдромом на тлі гіпотиреозу свідчить, що всі обстежені пацієнтки мали два і більше чинників ризику розвитку.…”
Section: Risk Factors Of Concomitant Pathology Development In Patientunclassified